(untitled) (Kairaranga, 2021)
Universal Design for Learning (UDL) is a framework for developing inclusive educational practices. The primary purpose of this small-scale professional inquiry was to investigate the effective ways in which Resource Teachers: Learning and Behaviour (RTLB) across New Zealand implement and evaluate the UDL framework in their practice to improve the educational achievement of all learners. The enablers and barriers to implementing UDL in practice were explored through an anonymous online questionnaire using a mixed-method approach. This study highlighted that RTLB were using the UDL principles in several areas at different stages of the RTLB practice sequence. The results indicated that ongoing professional learning development and collaboration within the organisation were the preferred modes of support to implement the UDL framework. RTLB also articulated several barriers to its implementation including teacher resistance and lack of knowledge. The need for more UDL training for educators was identified. Differences were found in ways of monitoring the UDL interventions amongst practitioners. The results further underlined the need for developing a clear criterion to monitor the application of UDL in practice.